2012
DOI: 10.5808/gi.2012.10.2.88
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Effects of Lipoprotein Lipase Polymorphisms with Lifestyle on Lipid Levels in a Korean Population: A Cross-sectional Study

Abstract: Lipoprotein lipase (LPL) plays an essential role in the regulation of high-density lipoprotein cholesterol (HDLC) and triglyceride levels, which have been closely associated with cardiovascular diseases. Genetic studies in European have shown that LPL single-nucleotide polymorphisms (SNPs) are strongly associated with lipid levels. However, studies about the influence of interactions between LPL SNPs and lifestyle factors have not been sufficiently performed. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Previous epidemiological studies found significant interactions of the LPL polymorphism with smoking (14), physical activity (14), alcohol consumption (12,15), and intake of dietary fat (15,16), although no significant interaction for alcohol consumption was reported (11). Inconsistent findings regarding alcohol consumption may be partly due to an unclear cause-and-effect relation in a cross-sectional design.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Previous epidemiological studies found significant interactions of the LPL polymorphism with smoking (14), physical activity (14), alcohol consumption (12,15), and intake of dietary fat (15,16), although no significant interaction for alcohol consumption was reported (11). Inconsistent findings regarding alcohol consumption may be partly due to an unclear cause-and-effect relation in a cross-sectional design.…”
Section: Discussionmentioning
confidence: 57%
“…Recently, genome-wide association (GWA) studies have revealed common genetic factors that are associated with the HDL-C concentration in blood and demonstrated strong evidence for the LPL gene involvement (7)(8)(9)(10). Furthermore, some cross-sectional studies have reported LPL gene-lifestyle interactions in association with HDL-C or TG concentrations (11)(12)(13)(14)(15)(16). However, such interactions have not been examined in prospective studies.…”
Section: Introductionmentioning
confidence: 95%
“…The associations between genotypes and phenotypes can be modified by gene-environment interactions. Effect modification of the associations between LPL SNPs and serum lipid concentrations by interactions with cigarette smoking has been reported (Lee et al, 2004;Kathiresan et al, 2008;Kooner et al, 2008;Pyun et al, 2012;Mo et al, 2013). In the present study, association of the LPL SNP with HDL cholesterol by smoking status was also examined.…”
Section: )mentioning
confidence: 69%
“…16 In support of this hypothesis, significant interactions have been observed between LPL gene polymorphisms and environmental factors, such as smoking, [17][18][19][20][21] gender, 17,22 alcohol consumption, 20 dietary, [23][24][25] physical activity 18,26 and obesity. 24,[27][28][29][30][31][32] However, results from other studies did not support some of these findings for interaction between LPL SNPs and smoking, 24,33,34 gender, 24 alcohol consumption, 24,33 dietary, 35,36 physical activity 20,25 and obesity. 20,37,38 The association between rs2197089 and lipid concentrations was less reported in the Chinese Han population, and so was the interaction of this SNP with risk factors on lipid concentrations.…”
Section: Introductionmentioning
confidence: 97%